Antifungal activity of silver nanoparticles on Fluconazole resistant Dermatophytes identified by (GACA)4 and isolated from primary school children suffering from Tinea Capitis in Ismailia – Egypt - Amin, Mariam E.; Azab, Marwa M.; Hanora, Amro M.; Abdalla, Salah (Cellular and Molecular Biology, 2017)
Fungal infections caused by dermatophytes recently became more common. Available antifungal drugs are limited because of emergence of resistant strains due to prophylaxis with them, so there is an urgent need for novel antifungals. This study is aimed to detect the antifungal activity of silver nanoparticles (SNPs) on Fluconazole resistant dermatophytes isolated from primary school children clinically suffering from tinea capitis and attending El-Sheikh Zaid Dermatology Center in Ismailia. The study was done on 112 clinical cases. Examination with potassium hydroxide(KOH) of hair samples was done, followed by routine identification using culturing, macroscopical and microscopical examination and biochemical tests, finally molecular identification using Polymerase Chain Reaction (PCR) with (GACA) 4 was done. Fluconazole resistance of these dermatophytes was detected by different methods including agar disc diffusion method and broth microdilution susceptibility testing. Silver nanoparticles susceptibility testing was carried out on these Fluconazole resistant dermatophytes. The Ubiquitin 1 (Ub 1) gene was detected in samples which were Fluconazole resistant but SNPs susceptible. In this study dermatophytes were found only in 70 samples (62.5%). They were belonged to 3 species: Trichophyton violaceum, Microsporum gypseum and Microsporum canis. Fluconazole resistance was found in 58 samples (82.85%). Both M. canis and M. gypseum were resistant to all used concentrations of SNPs, while T. violaceum was susceptible to 50 µg/ml SNPs solution. The Ub1 gene was detected in 1 sample (4.8%). Therefore SNPs can be used for treatment of T. violaceum, while they can’t be used for treatment of M. canis or M. gypseum.